Southwest monsoon onset dates over Malaysia and associated climatological characteristics - Chenoli, Sheeba Nettukandy; Jayakrishnan, P.R.; Samah, Azizan Abu; Ooi, See Hai; Ahmad Mazuki, Muhammad Yunus; Lim, Chai Heng (Elsevier, 2018)
In Malaysia precipitation prevails throughout the year. However, the southwest monsoon (late May to September) is characterised with low precipitation, less cloud, high outgoing long-wave radiation (OLR) and often featured by dry epochs. Therefore, onset of the monsoon here is best determined by considering multiple onset parameters such as wind, OLR, rainfall and relative humidity. We used modified Malaysian Meteorological Department wind shear index based on major convection centres during the monsoon onset. The 850 hPa winds were chosen to investigate the onsets of the monsoon in view of the marked orographic and mesoscale processes. The next criterion was the presence of sustained westerlies averaged between 850 hPa and 600 hPa from all the available radiosonde stations data over Malaysia for at least 5 days. As the strongest convective activity in the tropics is represented by OLR of less than 220 W m-2, the third criterion was to check whether the value of OLR was greater than 220 W m-2 over the region. The mean date of the summer monsoon onset over Malaysia is found to be 19 May, with a standard deviation of 8 days. Further, climatological composites show that there is a gradual change from easterlies to westerlies from the surface up to 500 hPa in Malaysian stations both in Peninsular Malaysia and East Malaysia during May. OLR and rainfall analysis reveal that, the southwest monsoon daily rainfall over Malaysia is less than 10 mm and OLR is greater than 220 W m-2. Additionally, monsoon onset tends to be late during the El Niño years and earlier during the La Niña years.